Early Screening and Identification of an Asymptomatic Pheochromocytoma in a Child with Von Hippel-Lindau: A Case Report - Kristine Schmeling; Jennifer Schuh; Dave Lal; Kerri Becktell (Case Reports in Oncology)
Introduction: Von Hippel-Lindau (VHL) is a diagnosis that leads to increased risk of tumor development over the course of a patient’s lifetime. Patients with VHL undergo screening for multiple tumor types, including pheochromocytomas (PCCs). There is variability among the different international guidelines regarding the age to begin PCC screening, with most suggesting 5 years for screening initiation. Case Presentation: Our patient is a 4-year-old female who underwent screening for PCC at the time of her VHL diagnosis while asymptomatic that identified a unilateral PCC. This was amendable to treatment with laparoscopic partial adrenalectomy. Conclusion: This is the first report of an asymptomatic PCC being identified in a patient under the age of 5. With early identification, this was treated surgically before it caused systemic symptoms with preservation of normal adrenal gland tissue. This supports adhering to the pediatric specific guidelines which recommend earlier initiation of PCC screening in pediatric patients with VHL.